P144: "I wasn't oriented a lot, so I'm essentially learning as I go": onboarding and transition to practice of new emergency physicians. (May 2019) - Yeung, M.; Cheung, W.; Hebert, G.; Gee, A.
Abstract : Introduction : Transition to the attending physician role and onboarding at a new workplace are often stressful. Effective initiation is important to individuals as well as departments, hospitals and universities wishing to retain valuable staff. Our aim was to learn about early experiences from the perspective of new staff and apply these findings to develop a new onboarding program.Methods : Following a pilot study of individual interviews, we surveyed and conducted focus group interviews with all attending physicians who had joined our dual site, urban, academic emergency department within three years. We used a mixed quantitative and qualitative approach to collect and analyze data. We applied the data to develop a new needs-based formal onboarding program.Results : 24/36 participated in the survey, 22/36 in focus groups. 95% were 30-39 years old. Newcomers described the existing orientation as too brief, non-specific, and missing essential elements. We identified six onboarding themes: (1)clinical protocols and reference documents, (2)graduated responsibilities, (3)mentorship, (4)relationship building, (5)department structure and culture, and (6)emotions. We formed a committee to develop and implement these initiatives: (1)a new online platform enables easy access to clinical care and orientation documents, (2)a formal mentorship program matches each newcomer with 2 mentors to coach towards goals, navigate department structure and culture, and provide perspective to mitigate strong emotions, (3)adjusting shift and teaching assignments allows newcomers to ease into clinical and academic responsibilities, and (4)our next priority is to improve clarity around academic opportunities, expectations, and advancement.Conclusion : New emergency physicians are highly engaged and provided many insights on their orientation experiences. Using mixed methods, we identified six themes to guide the design and implementation of a program to promote successful integration of newcomers.